Military chemical warfare agent human subjects testing: part 2--long-term health effects among participants of U.S. military chemical warfare agent testing. - Brown M; Brown, Mark (Military Medicine, 2009)
Military chemical warfare agent testing from World War I to 1975 produced thousands of veterans with concerns about how their participation affected their health. A companion article describes the history of these experiments, and how the lack of clinical data hampers evaluation of long-term health consequences. Conversely, much information is available about specific agents tested and their long-term health effects in other populations, which may be invaluable for helping clinicians respond effectively to the health care and other needs of affected veterans. The following review describes tested agents and their known long-term health consequences. Although hundreds of chemicals were tested, they fall into only about a half-dozen pharmaceutical classes, including common pharmaceuticals; anticholinesterase agents including military nerve agents and pesticides; anticholinergic glycolic acid esters such as atropine; acetylcholine reactivators such as 2-PAM; psychoactive compounds including cannabinoids, phencyclidine, and LSD; and irritants including tear gas and riot control agents.